The Integration of Descendants of Migrants from Turkey in Stockholm : The TIES Study in Sweden - Westin, Charles, 1941- (Book collections on Project MUSE., 2015)
This timely book, which is based on the results of the Integration of the Second Generation in Europe survey, presents the disturbing results of a recent study in Stockholm that examines the experiences of residents descended from Turkish migrants. Focusing on three different ethno-national groups-Turks, Kurds, and Syriacs-the contributors explore issues such as identity, family situation, language use, education, labor market experiences, and employment. The essays highlight the varying degrees of success each group has achieved in the process of trying to integrate into Stockholm society. The book also examines the widespread discrimination and exclusion the descendants of migrants experience. As a whole, this volume shows a troubling picture of the obstacles faced by immigrant new societies.